Inheritance of Quizalofop Resistance in a Smooth Barley Biotype from South Australia. (1st November 2017) - Shergill, Lovreet S.; Malone, Jenna; Boutsalis, Peter; Preston, Christopher; Gill, Gurjeet S.
Abstract : Core Ideas: The resistant population was 60‐fold resistant to quizalofop. Ile‐1781‐Leu mutation in the ACCase gene confers resistance to quizalofop. Quizalofop resistance is inherited by single, partially dominant nuclear allele. Smooth barley [ Hordeum glaucum (Steud.) Tzvelev] has recently evolved resistance to acetyl coenzyme‐A carboxylase (ACCase) inhibitors in crop fields of South Australia. Experiments were conducted to determine the inheritance of quizalofop (quizalofop‐p‐ethyl) resistance in a population of smooth barley. Resistant plants (pollen donor) were crossed with susceptible plants (pollen acceptor) to generate an F1 generation, and the F1 hybrid was selfed to produce an F2 generation. It was observed that the resistant population was >60‐fold more resistant to quizalofop as compared with the susceptible population and contained an amino acid change from isoleucine‐to‐leucine at 1781 in the carboxyl‐transferase domain of the ACCase gene. The F1 individual was confirmed to be heterozygous by sequencing the carboxyl‐transferase domain of ACCase, indicating that the inheritance of resistance is nuclear encoded. The F2 dose–response indicated that quizalofop resistance in smooth barley is conferred by a single partially dominant gene. The F2 plants segregated in a 3:1 ratio when treated with 6.2 g quizalofop ha −1, and sequencing of the ACCase gene also revealed that resistance alleles segregated in a 1:2:1 ratio, as expected for single‐gene inheritance. This study confirms that quizalofop resistance in smooth barley from Australia is inherited by a single, partially dominant nuclear allele encoding a mutation in ACCase that confers resistance at the field rate.